2009
DOI: 10.1007/s11664-009-0738-y
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes of the Ag-Epoxy ICA/Sn Interface in a High-Humidity Environment

Abstract: In the present study, the degradation of the Ag-epoxy conductive adhesive/Sn interface at 85°C and 85% relative humidity was investigated through a variety of microstructural analyses. After the humidity test, the interfacial electrical resistance increased, and the interface was easily separated by external stress. Transmission electron microscopic (TEM) analyses indicated that two different Sn oxides, namely SnO and SnO 2 , were formed inhomogeneously at the interface in the humidity test. In addition, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The formation of these two oxides corresponds well with the findings of our previous work using a model specimen. 17 Through the galvanic reaction, the surface of the Sn plating near the Ag fillers became corroded. 6,7 The formation of these Sn oxide layers can interfere with the electrical contact between the Ag filler and the Sn plating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these two oxides corresponds well with the findings of our previous work using a model specimen. 17 Through the galvanic reaction, the surface of the Sn plating near the Ag fillers became corroded. 6,7 The formation of these Sn oxide layers can interfere with the electrical contact between the Ag filler and the Sn plating.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] It has been reported that oxides with poor electrical conductivity such as Cu, Pb, and Sn oxide on Cu, Pb-Sn, and Sn plating, respectively, cause a decrease in the electrical conductivities of ICA joints in humid conditions. 6,7,17 Thus, the Sn oxide layers formed on the Sn plating undoubtedly cause the increase of electrical resistance.…”
Section: Relationship Between Electrical Resistance and Microstructurementioning
confidence: 99%